Lithium-Doped Biological-Derived Hydroxyapatite Coatings Sustain In Vitro Differentiation of Human Primary Mesenchymal Stem Cells to Osteoblasts - (:unkn) unknown (MDPI, 2019)
This study is focused on the adhesion and differentiation of the human primary mesenchymal stem cells (hMSC) to osteoblasts lineage on biological-derived hydroxyapatite (BHA) and lithium-doped BHA (BHA:LiP) coatings synthesized by Pulsed Laser Deposition. An optimum adhesion of the cells on the surface of BHA:LiP coatings compared to control (uncoated Ti) was demonstrated using immunofluorescence labelling of actin and vinculin, two proteins involved in the initiation of the cell adhesion process. BHA:LiP coatings were also found to favor the differentiation of the hMSC towards an osteoblastic phenotype in the presence of osteoinductive medium, as revealed by the evaluation of osteoblast-specific markers, osteocalcin and alkaline phosphatase. Numerous nodules of mineralization secreted from osteoblast cells grown on the surface of BHA:LiP coatings and a 3D network-like organization of cells interconnected into the extracellular matrix were evidenced. These findings highlight the good biocompatibility of the BHA coatings and demonstrate that the use of lithium as a doping agent results in an enhanced osteointegration potential of the synthesized biomaterials, which might therefore represent viable candidates for future in vivo applications.
Keywords: biological-derived hydroxyapatite coatings; lithium doping; pulsed laser deposition; human mesenchymal stem cells; osteoblasts; ALKALINE-PHOSPHATASE; THIN-FILMS; BONE; TITANIUM; ADHESION; ATTACHMENT; SCAFFOLDS; SURFACES